Modulatory Effect of Synbiotic and/or Antibiotic on Biochemical Indices, Gene Expression and Meat Quality of Broiler Chicken Challenged with Clostridium Perfringens - Mohamed, Haidy E.; Gaafar, Rehab E.M.; Ibrahim, Wafaa A.A.; Hassan, Heba M. (Journal of Advanced Veterinary Research, 2023)
Synbiotic and/or antibiotic supplementation effect on biochemical parameters, gene expression, meat quality, and antibiotic residues were evaluated in this study involving broilers challenged with Clostridium perfringens bacteria. A total of 120 one-day chicks were divided into five groups. Group A and B were control negative and control positive. Group C supplemented with synbiotic (PoultryStarÂ®). Group D supplemented with antibiotic (FlagymoxÂ®). Group E supplemented with mixed antibiotic and synbiotic. On the 14th day, all groups except group A were inoculated with Clostridium perfringens bacteria. Supplementation of synbiotic alone or in combination with antibiotic resulted in improving the serum protein and albumin levels, glucose concentrations, liver enzymes (AST, ALT and ALP), serum creatinine, uric acid, oxidative and anti-oxidative activities (decrease MDA and increased SOD, CAT and GPx activities). The expression of IL10, CAT, SOD and GPx mRNA was upregulated. Additionally, there was an improvement in meat quality (elevated protein and low fat contents and reduced TBARS contents, with no effect on moisture or ash content). However, antibiotic supplementation revealed antibiotic residues in meats of broilers. In conclusion, synbiotic supplementation shows potential in mitigating necrotic enteritis and can play role as alternative to antibiotics for broilers infected with Clostridium perfringens.